The concept of structure and content of health related trainings for higher educational establishments’ students - Yu.A. Kopylov; L.N. Jackowska; M.D. Kudryavtsev; V.A. Kuzmin; I.A. Tolstopyatov; S. S. Iermakov (Physical Education of Students, 2015)
Purpose: analysis of modern directions of physical culture education scientific and practical problems’ solution in higher educational establishment of health related orientation. Material: analysis of publications in scientific journals. Results: we have shown significance of student’s physical functioning as the basis of his motor, coordination and mental qualities’ development. Main difficulties of existing physical education practice have been cleared up. It has been found that prevailing training of physical qualities at physical culture classes does not solve the problem of students’ health strengthening. Ways to application of additional health related physical culture trainings have been shown. Transition to such trainings opens opportunities for creation a new concept, permits to effectively and relatively quickly implement its main ideas and principles in practice of HEE education. Conclusions: content of additional (health related) physical culture training envisages prevailing orientation on health related, general developing and sport-recreational tasks. With it first attention shall be paid to formation of physical, psychic and social-moral health as well as to personality-oriented approach in system of individual choice of physical culture means.